Oral White Sponge Nevus: An Exceptional Differential Diagnosis in Childhood - Fatima zahra Elfatoiki; Sophia Capatas; Hayat Dahbi Skali; Fouzia Hali; Hicham Attar; Soumia Chiheb (Hindawi Limited, 2020)
White sponge nevus is an autosomal dominant skin disorder characterized by white, irregular, diffuse plaques mainly affecting the oral mucosa. Histological findings of white sponge nevus are characteristic but not pathognomonic. We report a case of an oral white sponge nevus in a 6-year-old girl, which poses a problem in differential diagnosis with oral candidiasis. No treatment was performed because of the benign and asymptomatic nature of the lesions.